2023
DOI: 10.1002/ptr.7788
|View full text |Cite
|
Sign up to set email alerts
|

Safflower yellow and its main component hydroxysafflor yellow A alleviate hyperleptinemia in diet‐induced obesity mice through a dual inhibition of the GIP‐GIPR signaling axis

Abstract: Glucose‐dependent insulinotropic polypeptide (GIP) is a gastrointestinal hormone secreted by K cells in the small intestine and is considered an obesity‐promoting factor. In this study, we systematically investigated the anti‐obesity effects of intragastric safflower yellow (SY)/hydroxysafflor yellow A (HSYA) and the underlying mechanism for the first time. Our results showed that intragastric SY/HSYA, rather than an intraperitoneal injection, notably decreased serum GIP levels and GIP staining in the small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…It was well established that hypocaloric diet was the cornerstone of treatment for MAFLD [ 57 , 59 ]. Our study found that intragastric SY obviously reduced the food intake of DIO mice during the intervention, which has also been found in our previous results [ 38 ]. Our further correlation analysis of the metabolic phenotypes and gut microbiota showed that Bacteroides, Bacteroides_acidifaciens and Bacteroides_intestinalls were negatively correlated with food intake of DIO mice, while their abundance was significantly increased in SY-treated mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was well established that hypocaloric diet was the cornerstone of treatment for MAFLD [ 57 , 59 ]. Our study found that intragastric SY obviously reduced the food intake of DIO mice during the intervention, which has also been found in our previous results [ 38 ]. Our further correlation analysis of the metabolic phenotypes and gut microbiota showed that Bacteroides, Bacteroides_acidifaciens and Bacteroides_intestinalls were negatively correlated with food intake of DIO mice, while their abundance was significantly increased in SY-treated mice.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study indicated intragastric SY/HSYA, rather than an intraperitoneal injection, notably decreased serum Gip levels and Gip staining in the small intestine in diet-induced obese (DIO) mice [ 38 ], suggesting intragastric intervention played an important role in gut. Given the important role of gut microbiota plays in the occurrence and development of MAFLD and the potential link between the effects of SY and gastrointestinal tract, the potential contributions of gut microbiota to the benefits of SY treatment on MAFLD were investigated in our present study.…”
Section: Discussionmentioning
confidence: 99%